Perceptions and practices on healthy and unhealthy eating among selected urban and rural young children - Soriano, Ma. Andrea L.; Gabriel, Florenda S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
This study sought to identify the similarities and differences of perceptions and practices on healthy and unhealthy eating among selected young children in urban and rural areas. The study consisted of young children, 2 ½ 6years old, who were purposively selected. The urban group was composed of 15 children from San Vicente Elementary School, Quezon City while the 15 children from the rural group were from four schools in the province of Tarlac. Informed consent from the school and the parents of the children were secured before data collection. Data was collected through an interview with the use of pictures of food to gather data on consumption of perceived healthy and unhealthy food. Content analysis and descriptive statistics were used to analyze the results of this study. Results show that rural children have better perceptions of healthy and unhealthy foods compared to the urban children. Both urban and rural children have good perceptions of healthy eating routine, such as appropriate meal frequency, venue of eating, acceptable/unacceptable mealtime activities. Children reported parents, teachers and media as sources of information but some negative ways of teaching, such as lecturing and force feeding were experienced by the children. Both urban and rural young children have good practices in terms of food consumption patterns, breakfast and snack mealtimes, and meal frequencies. Relatively short mealtime duration and doing unacceptable mealtime activities were reported by the children. The study recommends more directed nutrition education in public schools especially in the urban poor areas as well as appropriate parental feeding practices.
Thesis Classification: F
Thesis (B.S. Home Economics)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Preschool children -- Philippines -- Nutrition; Children -- Nutrition -- Psychological aspects